CLINICAL AND DIAGNOSTIC CRITERIA OF CHRONIC PELVIC PAIN IN PATIENTS WITH OVARIAN BENIGN TUMORS - Сергей Владимирович Баринов; Оксана Вячеславовна Лазарева; Юлия Игоревна Тирская; Татьяна Владимировна Кадцына; Юрий Игоревич Чуловский; Анастасия Дмитриевна Орлицкая; Егор Андреевич Хорошкин; Людмила Леонидовна Шкабарня; Максим Николаевич Грицюк (The Publishing House Medicine and Enlightenment, 2024)
Aim of the study - to analyze the history, symptoms, laboratory and ultrasound data in patients with chronic pelvic pain associated with benign ovarian tumors. Materials and methods. This retrospective controlled study included 102 patients with benign ovarian tumors: group A (n = 48) included patients with histologically approved ovarian endometriomas (OMA), group B (n = 54) included patients with non-endometrioid benign ovarian tumors. Results. The mean age of the patients (n = 102) was 36,9 (6,9) years old. The severity of pain accessed via visual analogue scale (VAS) in patients from group A was significantly higher than in patients from group B - 4 [2; 5,5] и 3 [1; 4] respectively (U = 950,0; p = 0.028). The occurrence of infertility (χ2 = 5,255; p = 0,022), dysmenorrhea (χ2 = 4,410; p = 0,036), non-cyclic uterine bleeding (χ2 = 5,255; p = 0,022) was significantly higher in group A than in group B. The levels of CA-125 were significantly higher in patients from group A (U = 286,0; p = 0,004). The following ultrasound symptoms were found significantly more often in patients from group A: size of the tumor less than 60 mm (χ2 = 7,321; p = 0,007), hypechoic cysts (χ2 = 71,470; p < 0,001), ground glass echogenicity (χ2 = 55,800; p < 0,001). Intraoperatively adhesions were found significantly more often in women from group A (χ2 = 17,761; p < 0,001). Conclusion. Women with ovarian endometriomas have a more severe pelvic pain. Occurrence of infertility in patients with OMA is significnantly higher than in patients with nonendometrioid ovarian tumors. Adhesions are found more often in patients with OMA than in patients with nonendometrioid benign tumors.